London International Consensus and Delphi study on hamstring injuries part 2: operative management. (17th January 2023) - Plastow, Ricci; Kerkhoffs, Gino M M J; Wood, David; Paton, Bruce M; Kayani, Babar; Pollock, Noel; Court, Nick; Giakoumis, Michael; Head, Paul; Kelly, Sam; Moore, James; Moriarty, Peter; et al.
Abstract : The key indications for surgical repair of hamstring injuries (HSIs) remain unclear in the literature due to a lack of high-level evidence and expert knowledge. The 2020 London International Hamstring Consensus meeting aimed to highlight clear surgical indications and to create a foundation for future research. A literature review was conducted followed by a modified Delphi process, with an international expert panel. Purposive sampling was used with two rounds of online questionnaires and an intermediate round involving a consensus meeting. The initial information gathering (round 1) questionnaire was sent to 46 international experts, which comprised open-ended questions covering decision-making domains in HSI. Thematic analysis of responses outlined key domains, which were evaluated by a smaller international subgroup (n=15) comprising clinical academic sports medicine physicians, physiotherapists and orthopaedic surgeons in a consensus meeting. After group discussion of each domain, a series of consensus statements were prepared, debated and refined. A round 2 questionnaire was sent to 112 international hamstring experts to vote on these statements and determine level of agreement. The consensus threshold was set a priori at 70% agreement. Rounds 1 and 2 survey respondents were 35/46 (76%) and 99/112 (88.4%), respectively. The consensus group agreed that the indications for operative intervention included: gapping at the zone of tendinous injury (87.2% agreement) and loss of tension (70.7%); symptomatic displaced bony avulsions (72.8%); and proximal free tendon injuries with functional compromise refractory to non-operative treatment (72.2%). Other important considerations for operative intervention included: the demands of the athlete/patient and the expected functional outcome (87.1%) based on the anatomy of the injury; the risk of functional loss/performance deficit with non-operative management (72.2%); and the capacity to restore anatomy and function (87.1%). Further research is needed to determine whether surgery can reduce the risk of reinjury as consensus was not reached within the whole group (48.2%) but was agreed by surgeons (70%) in the cohort. The consensus group did not support the use of corticosteroids or endoscopic surgery without further evidence. These guidelines will help standardise treatment of HSIs, specifically the indications and decision-making for surgical intervention.